Le Thesaurus Occitan, une base de données multimédiale dédiée aux dialectes occitans - Guylaine Brun-Trigaud (La Bretagne Linguistique, 2014)
The Thesaurus Occitan is a computer database set up for the study of Occitan dialects. It contains linguistic and perilinguistic data drawn from field surveys, which mainly comprise maps, monographs and Atlas Linguistiques Régionaux survey notebooks. It also includes multimedia content, represented by sound recording extracts and iconographic documents. The linguistic data in the database are analysed by lemmatisation, morphology, etymology and microtoponymy. Finally, the database provides analytical tools such as cartographic representations, diachronic analysis tools, comparative cartography procedures and morphological analysis tools.